2019
DOI: 10.2147/idr.s195144
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of pegylated interferon monotherapy and de novo pegylated interferon plus tenofovir combination therapy in patients with chronic hepatitis B</p>

Abstract: Background and aim: We aimed to evaluate the effectiveness of pegylated interferon (Peg-IFN) monotherapy (IFN group) and combination therapy with tenofovir (TDF) and Peg-IFN (IFN+TDF group) in chronic hepatitis B (CHB) patients. Patients and methods: Data of 143 CHB patients were analyzed in this study. All patients enrolled received liver biopsy. Virologic responses were defined as hepatitis B virus (HBV) DNA <100 IU/mL, biochemical responses were defined as normalization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Pretreatment HBsAg, viral load and ALT levels were highlighted to predict post-treatment response of IFN therapy. For CHB patients with pretreatment high ALT level, low viral load and low HBsAg level, treatment with IFN leads to better clinical outcomes [25][26][27][28]. Consistent with previous studies, in our study, we found that baseline ALT >4×ULN, HBV DNA <2×106 IU/mL and HBsAg <25000 IU/mL were significantly associated with EOT HBsAg ≤10 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Pretreatment HBsAg, viral load and ALT levels were highlighted to predict post-treatment response of IFN therapy. For CHB patients with pretreatment high ALT level, low viral load and low HBsAg level, treatment with IFN leads to better clinical outcomes [25][26][27][28]. Consistent with previous studies, in our study, we found that baseline ALT >4×ULN, HBV DNA <2×106 IU/mL and HBsAg <25000 IU/mL were significantly associated with EOT HBsAg ≤10 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…Pretreatment HBsAg, viral load and ALT levels were highlighted to predict post-treatment response of IFN therapy. For CHB patients with pretreatment high ALT level, low viral load and low HBsAg level, treatment with IFN leads to better clinical outcomes [24][25][26][27]. Consistent with previous studies, in our study, we found that baseline ALT > 4 × ULN, HBV DNA < 2 × 106 IU/mL and HBsAg < 25,000 IU/mL were significantly associated with EOT HBsAg ≤10 IU/mL.…”
Section: Discussionsupporting
confidence: 90%
“…All subjects finished the questionnaire surveys in a quiet room without any interference or disruptions. Professional staff members were available to answer ques-tions if any problems occurred in understanding the survey questions 21 .…”
Section: Sociodemographic Informationmentioning
confidence: 99%